Imatinib mesylate lacks efficacy in relapsed/refractory peripheral T cell lymphoma. Issue 4 (April 2015) - Jacobsen, Eric; Pozdnyakova, Olga; Redd, Robert; Fisher, David C.; Dorfman, David M.; Dal Cin, Paola; LaCasce, Ann; Armand, Philippe; Hochberg, Ephraim; Cote, Gregory; Shahsafaei, Ali; Neuberg, Donna; et al.
Abstract Platelet derived growth factor-α (PDGFR-α) is expressed in peripheral T cell lymphoma, not otherwise specified (PTCL, NOS). Imatinib mesylate demonstrated in vitro cytotoxicity against primary PTCL, NOS cells. We initiated a trial of imatinib in 12 patients with relapsed or refractory T-cell non-Hodgkin lymphoma (T-NHL). PDGFR-α expression by immunohistochemistry and fluorescence in situ hybridization (FISH) to assess for FIP1L1–PDGFR-α fusion and/or PDGFR-α amplification were not required for study entry. We documented no objective responses. The median progression-free survival was 21.0 days (90% confidence interval [CI] 15.0, 28.0) and median overall survival was 154 days (90% CI 35, 242). Four patients had tissue available for analysis of PDGFR-α by immunohistochemistry and three of these patients' tumors expressed PDGFR-α. Imatinib was not effective for the treatment of peripheral T cell lymphoma in an unselected group of patients in which PDGFR-α expression was not required for study entry.